2020
DOI: 10.1021/acsanm.0c00190
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon–Metal Organic Framework Composite for the Adsorption of Contaminants of Emerging Concern from Water

Abstract: A composite adsorbent (CMOF) based on in situ growth of MIL-100Fe (MOF) within the macro-and mesopores of a Darco-KB-G activated carbon (AC) was prepared for the efficient adsorption of a set of contaminants of emerging concern (CECs), namely, caffeine (CFN), carbamazepine (CBZ), clofibric acid (CA), 10,11-epoxycarbamazepine (Ep-CBZ), naproxen (NPX), o-desmethylnaproxen (o-DMN), paraxanthine (PXN), and salicylic acid (SA), from water. The properties of the composite and that of the parent materials were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 70 publications
0
15
0
1
Order By: Relevance
“…As shown in Figure 1c, for U0.2Z0.8, the growth of small UiO-66-NH2 particles occurred on the surface of beta-ZTC. It has been reported that MOFs are located in the pores or void spaces of activated carbon in MOF-carbon composites [33]. However, in U0.2Z0.8, the UiO-66-NH2 nanoparticles were dispersed on the surface of beta-ZTC, likely because beta-ZTC has micropores with sizes between 0.7 and 1.0 nm.…”
Section: Characterization Of Uio-66-nh2/ztc Composites and Pristine Materialsmentioning
confidence: 95%
“…As shown in Figure 1c, for U0.2Z0.8, the growth of small UiO-66-NH2 particles occurred on the surface of beta-ZTC. It has been reported that MOFs are located in the pores or void spaces of activated carbon in MOF-carbon composites [33]. However, in U0.2Z0.8, the UiO-66-NH2 nanoparticles were dispersed on the surface of beta-ZTC, likely because beta-ZTC has micropores with sizes between 0.7 and 1.0 nm.…”
Section: Characterization Of Uio-66-nh2/ztc Composites and Pristine Materialsmentioning
confidence: 95%
“…Carbon materials (CMs), such as graphene oxide (GO), [89] activated carbon (AC) [90] and carbon nanotubes (CNTs), [91] were extensively used in the preparation of substantial nanocomposites due to their porous characteristics and great chemical stability. [92] For instance, Co-Ni MOFs/3D graphene (Co-Ni c) Reproduced with permission.…”
Section: Mof@carbon Materialsmentioning
confidence: 99%
“…Muñoz-Senmache et al [69] have shown that it is possible to address the limitations of MOFs using the same in situ growth principle that was used for the preparation of CFAU hierarchical composites. Muñoz-Senmache et al successfully grew a MIL-100Fe MOF phase within the meso-and macro-pores of activated carbon (CMOF; Figure 5).…”
Section: Hierarchical Composites Via Confined-space Synthesismentioning
confidence: 99%
“…Fernández-Reyes et al tested the thermal regeneration of Cu 2+ -CFAU in a vacuum atmosphere, while Muñoz-Senmache, et al developed a thermal treatment of CMOF under nitrogen gas. Both adsorbents were tested for multi-cycle adsorption of naproxen Adsorbent materials: polymeric resin [71], linoptilolite [74], palygorskite [74], mesoporous silica (SBA-15) [53], copper amine-functionalized mesoporous silica (Cu-NH 2 _g_SBA-15) [53], hexagonal mesoporous silica (HMS) [61], aminefunctionalized hexagonal mesoporous silica (A-HMS) [61], mercapto-functionalized hexagonal mesoporous silica (M-HMS) [61], activated carbon (AC1) [61], cork [79], granular activated carbon coal-based Calgon Filtrasorbs 400 (F400) [78], coconut shell based PICACTIF TE activated carbon (CTIF-AC) [78], biochar [81], MIL-100Fe (MOF) [69], MIL-100Fe-activated carbon composite (CMOF) [69], activated carbon (AC) [56], detemplated FAU zeolite-activated carbon composite (CFAU) [56], and copper (II) containing FAU-zeolite/carbon composites (Cu-CFAU) [56]. and carbamazepine, respectively, and the results showed that the adsorption capacities remained constant even after three cycles.…”
Section: Regenerationmentioning
confidence: 99%
See 1 more Smart Citation